Chemotherapy and hemostasis disorders - E. V. Slukhanchuk; V. O. Bitsadze; A. G. Solopova; J. Kh. Khizroeva; K. N. Grigoreva; N. R. Gashimova; N. A. Makatsariya; D. V. Blinov; V. N. Galkin; A. Yu. Shatilina; E. M. Lyadnova; N. A. Shulga; et al. (Акушерство, гинекология и репродукция)
Cancer patients are at risk of developing arterial and venous thrombosis during chemotherapy (CT) and after its cessation. A prothrombotic risk may arise via pathogenetic pathways such as activation of external and internal coagulation pathways, decreased anticoagulant levels, platelet activation, fibrinolysis blockade, etc. Chemotherapeutic agents exert direct cytotoxicity, as well as indirectly suppress cellular processes necessary for tumor cell proliferation. CT-related cytotoxicity act on both tumor and healthy body cells. Available targeted drugs with improved selectivity for tumor cells are also associated with thrombosis risk. Low molecular weight heparins, which effectively reduce the risk of venous thromboembolism, have not yet been officially recommended for routine use during CT. Here, we discuss the prothrombotic effects of various antitumor agents aimed at gaining deeper understanding of the underlying mechanisms that may allow to develop new strategies for prevention and treatment of such formidable complications.